Real-world safety comparison between cenobamate and lacosamide: a pharmacovigilance study based on the FDA Adverse Event Reporting System - Shang, Shenglan; Chen, Dongxin; Song, Zhirui; Zhou, Chengrui; Chang, Qiuyue; Xiang, Lu; Yu, Mengchen; Zhao, Yan; Li, Weiliang; Zhou, Fan; Yu, Airong (Frontiers in Neurology, 2025)
BackgroundCenobamate (CNB) and lacosamide (LCM) are two common used third-generation anti-seizure medications (ASMs) for third-line treatment of the drug-resistant epilepsy. The real-world data on adverse events (AEs) related to them remains limited.MethodsAll data obtained from the US Food and Drug Administration Adverse Event Reporting System (FAERS) database, covering the period from 2008 to 2024. The reporting odds ratio, proportional reporting ratio and bayesian confidence propagation neural network to assess and compare the safety signals of CNB and LCM for comparison.ResultsA total of 50,323,324 AE reports were recorded, with 3,584 for CNB and 13,874 for LCM. The most significant signals were primarily in nervous system and psychiatric disorders, resembling those of traditional sodium channel blockers. Unreported AEs in the drug dispensatory were identified in LCM (multiple-drug resistance). Notable differences between LCM and CNB emerged: Certain numbers of AE signals associated with LCM were found in cardiac disorders, while no such relevant signals were detected for CNB; among the signals that detected in both drugs, most signals from CNB are stronger than those from LCM; The initial titration dose of CNB (12.5 mg, qd) reported a significantly higher number of AEs compared to the other dose groups.ConclusionChoosing the right ASMs requires consideration of the type of epilepsy, the individual tolerance and potential severe toxicity of different medications. Although the disproportionality analysis is a hypothesis generating, we provide a reference for the clinical safety of CNB and LCM.